Gaya Komunikasi Matematis Mahasiswa dalam Menyampaikan Materi Pertidaksamaan Melalui Video Pembelajaran Interaktif - Fadhila Kartika Sari; Anies Fuady (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Communication style is a way in which a person conveys messages or information. Pre-service teachers need to have good communication skills. Communication is one of the keys to the effectiveness of a learning process. Mathematical communication is divided into two, namely written communication and oral communication. Interactive learning videos are one of the alternative media used in online learning. This study aims to describe the mathematical communication style of pre-service teachers in conveying the material of Inequalities through interactive learning videos. This study uses a qualitative approach. The purposive sampling technique was chosen as the sampling method. The subjects of this study consisted of three students from the mathematics education study program FKIP UNISMA, each of which represented a different cohort level, namely semesters 2, 4, and 6. The results of the three subjects have a distinctive and different communication style in explaining the material of Absolute-Value Inequalities. Based on data analysis, the first student’s communication style tends to be non-assertive, the second student has a manipulative communication style, and the third student’s communication style tends to be more assertive.